(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study aims to assess the impact of various doses of ZIP on pancreas of male albino rats. Sixty male albino rats were assigned to three groups (10 animals/ group). Control group (1) received standard diet and water, group 2 and group 3 received for 30 days Under light microscope no tissue changes were seen in pancreas of control group. In group 2 ZIP causes pancreas vascular congestion of the islets of Langerhans, increase in the size of the islets, besides, necrosis of Langerhans cells. In group 3 ZI/P leads to pancreatic tissue revealed reduction in the size of the, vacuolation and degeneration of their cells, necrosis of other islets with mononuclear inflammatory cells infiltration and degenerative changes of pancreatic acini. It is concluded that administration of ZIP to rats for 30 days will affect the histological structure of pancreas and this effect is a dose dependent.